2000
DOI: 10.2308/iace.2000.15.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Perry Drug Stores, Inc.: Accounting and Control Issues for Inventory in a Retail Environment

Abstract: This case recounts an actual sequence of events that unfolded in the early 1990s. The facts of this case were drawn primarily from two enforcement releases issued by the Securities and Exchange Commission (viz., AAER Nos. 1015 and 1037) and from the 1991–1994 annual reports of Perry Drug Stores, Inc. In 1992, Perry Drug Stores ranked as the 14th largest drug store chain in the nation. During that year, Perry's management discovered that the company's inventory was significantly overstated. Physical inventories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Finally, a review of four leading accounting education journals for the period 2000-2002 (Watson et al, 2003) revealed the paucity of research devoted to the AIS course. Their review noted one article discussing the use of process mapping (Jones and Lancaster, 2001), one article examining student perceptions toward technology (Bhattacharjee and Shaw, 2001), and one AIS instructional case (Knapp and Knapp, 2000), suggesting that there is ample room for more research in this important area. …”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Finally, a review of four leading accounting education journals for the period 2000-2002 (Watson et al, 2003) revealed the paucity of research devoted to the AIS course. Their review noted one article discussing the use of process mapping (Jones and Lancaster, 2001), one article examining student perceptions toward technology (Bhattacharjee and Shaw, 2001), and one AIS instructional case (Knapp and Knapp, 2000), suggesting that there is ample room for more research in this important area. …”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Unknown/unexplained shrinkage is the inventory shortage identified following a physical stock-take. The findings from a physical audit take precedent over the book stock record (Knapp and Knapp, 2000), with the difference between the two numbers being the amount of the inventory shortage.…”
Section: Known and Unknown Shrinkagementioning
confidence: 99%
“…Knapp and Knapp (2000), show that the computer can be effectively used as a case study simulator by integrating ACL audit software into the financial statement auditing class. The use of computer software for case studies in the classroom teaches students skills such as critical thinking, problem solving and analytical thinking (Knapp & Knapp 2000).…”
Section: Computers In the Learning Processmentioning
confidence: 99%
“…Knapp and Knapp (2000), show that the computer can be effectively used as a case study simulator by integrating ACL audit software into the financial statement auditing class. The use of computer software for case studies in the classroom teaches students skills such as critical thinking, problem solving and analytical thinking (Knapp & Knapp 2000). This is especially useful where learning strategies must be emphasized, where there is a need for understanding rather than memorization, and unstructured problems are addressed (Bagranoff 1993).…”
Section: Computers In the Learning Processmentioning
confidence: 99%